IN VITRO EFFICACY TESTING OF NEEM (AZADIRACHTA INDICA) EXTRACT AGAINST AEROBIC AND ANAEROBIC BACTERIA - S. R., AKSHAYA; BHUVANESHWARI, G.; GRACE, J. R. LILLY; VENNILA, ROSY (International Journal of Current Pharmaceutical Research, 2020)
Objective: To experiment the antimicrobial susceptibility of crude extract from neem (Azadirachta indica) leaves against Staphylococcus aureus, Escherichia coli and Clostridium perfringens. Methods: Through the water extraction method, the aqueous crude extract of neem leaves were obtained. Separate colonies of Staphylococcus aureus, Escherichia coli and Clostridium perfringens were isolated and identified on different agars. Agar cup diffusion method was done to test the antimicrobial susceptibility of the neem leaves crude extract against those bacteria on Mueller-Hinton agar. Susceptibility was determined based on the zone of inhibition formed on the agar of each bacterium culture. Result: Neem was effective against Staphylococcus aureus and Clostridium perfringens. It was not effective against Escherichia coli. Conclusion: Neem extract has some promisable antimicrobial effects against Staphylococcus aureus and Clostridium perfringens causative bacterial infections.